Quel avenir pour le journalisme européen ? - Michel Mathien (Communication)
As a goal in the construction of the European Union, “European journalism” is a noble project. It cannot be separated from the debates about the future and the current changes of professionals working in mass media. The work of journalists is a part of the choices of businesses, themselves stakeholders in economic rationales that are more or less dependent on national markets, as well as the specific policies of each member-state of the European Union or the Council of Europe. The same is true with the uses or exploitations of cultures and identities as carried in their areas of circulation, which are more or less dominated by the symbolism of the nation-state. In a complex environment, journalists are far from acting in a “pure and perfect” situation to mediate between “their” public citizens and the political and economic actors. “European journalism” implies an absence of mutual clichés and stereotypes, and therefore a “multiperspectivity” of viewpoints.